Ruptures and continuities of rural extension in Argentina (1973-1983) (Quinto Sol, 2017)
The purpose of this paper is to study the activities of rural extension conducted between 1973 and 1983 by one of the main Argentinean state agencies: the National Agricultural Technology Institute (INTA). Regarding this period, which starts and ends with a democratic transition, an analysis has been made on the content and perspective of the organization’s rural extension agenda in relation to the transformations seen in matters of sectoral policies, socioeconomic changes in the rural area, and in the implementation of repressive mechanisms. There has been an evaluation on the operation of INTA’s state bureaucracy throughout its processes of institutional reconfiguration: one in 1973 alongside that year’s democratic transition and the other in 1976 in hand with Argentina’s last dictatorship. In light of documentary sources and interviews, a review has been drafted on institutional directives, nationwide coordination of agricultural policies, and the experiences of the INTA extension workers, primarily located in the Buenos Aires province. Additionally, we have identified the existence of various practices during the previous years of the last dictatorship involving direct contact with rural populations different from those of a more traditional approach, and its limitations have also been highlighted. Finally, we have analyzed the reorientation of the institution rural extension tasks as it underwent a military intervention between 1976 and 1983.
Keywords: rural extension systems; dictatorship; Argentina; rural population; bureaucracy